Inactivation of O(6)-alkylguanine-DNA alkyltransferase by folate esters of O(6)-benzyl-2′-deoxyguanosine and of O(6)-[4-(hydroxymethyl)benzyl]guanine - Javanmard, Sahar (2007)
O(6)-Alkylguanine-DNA alkyltransferase (alkyltransferase) provides an important source of resistance to some cancer chemotherapeutic alkylating agents. Folate ester derivatives of O(6)-benzyl-2′-deoxyguanosine and of O(6)-[4-(hydroxymethyl)benzyl]guanine were synthesized and tested for their ability to inactivate human alkyltransferase. Inactivation of alkyltransferase by the γ folate ester of O(6)-[4-(hydroxymethyl)benzyl]guanine was similar to that of the parent base. The γ folate esters of O(6)-benzyl-2′-deoxyguanosine were more potent alkyltransferase inactivators than the parent nucleoside. The 3′ ester was considerably more potent than the 5′ ester and was more than an order of magnitude more active than O(6)-benzylguanine, which is currently in clinical trials to enhance therapy with alkylating agents. They were also able to sensitize human tumor cells to killing by 1,3-bis(2-chloroethyl)-1-nitrosourea with O(6)-benzyl-3′-O-(γ-folyl)-2′-deoxyguanosine being most active. These compounds provide a new class of highly water-soluble alkyltransferase inactivators and form the basis to construct more tumor specific and potent compounds targeting this DNA repair protein.